PATHOPHYSIOLOGY OF ERYTHROCYTES FROM PATHOLOGICAL PHYSIOLOGY POSTHEMORRHAGIC AND HEMOLYTIC ANEMIAS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Anemia is a global hematologic condition that significantly affects oxygen transport and systemic homeostasis. Posthemorrhagic and hemolytic anemias are characterized by distinct mechanisms leading to erythrocyte loss and dysfunction. This article provides an in-depth analysis of erythrocyte alterations in these conditions, including membrane deformability, ion transport abnormalities, oxidative stress, and metabolic disruption. The clinical implications, compensatory mechanisms, and therapeutic strategies are discussed based on current English-language scientific literature. Understanding these processes is crucial for accurate diagnosis, management, and the development of innovative treatments.